The Impact of Tangible User Interfaces on Designers' Spatial Cognition - Kim, Mi Jeong; Maher, Mary Lou (Human-computer interaction, 2008)
Most studies on tangible user interfaces for the tabletop design systems are being undertaken from a technology viewpoint. Although there have been studies that focus on the development of new interactive environments employing tangible user interfaces for designers, there is a lack of evaluation with respect to designers' spatial cognition. In this research we study the effects of tangible user interfaces on designers' spatial cognition to provide empirical evidence for the anecdotal views of the effect of tangible user interfaces. To highlight the expected changes in spatial cognition while using tangible user interfaces, we compared designers using a tangible user interface on a tabletop system with 3D blocks to designers using a graphical user interface on a desktop computer with a mouse and keyboard. The ways in which designers use the two different interfaces for 3D design were examined using a protocol analysis method. The result reveals that designers using 3D blocks perceived more spatial relationships among multiple objects and spaces and discovered new visuo-spatial features when revisiting their design configurations. The designers using the tangible interfaces spent more time in relocating objects to different locations to test the moves, and interacted with the external representation through large body movements implying an immersion in the design model. These two physical actions assist in designers' spatial cognition by reducing cognitive load in mental visual reasoning. Further, designers using the tangible interfaces spent more time in restructuring the design problem by introducing new functional issues as design requirements and produced more discontinuities to the design processes, which provides opportunity for reflection and modification of the design. Therefore this research shows that tangible user interfaces changes designers' spatial cognition, and the changes of the spatial cognition are associated with creative design processes.